PEMAHAMAN PENGAJARAN MENGENAI PASKAH DALAM PENGUATAN IMAN DI GEREJA KRISTEN SETIA INDONESIA (GKSI) KECAMATAN KUALA BEHE - Tony Salurante; Semuel Linggi Topayung; Riswan Riswan (Jurnal PKM Setiadharma, 2022)
An understanding of the Work of Christ for believers has great significance. Theologically the work of Christ in death, resurrection and ascension is a series that influences many doctrines in Christianity. But for the Indonesian Faithful Christian Church members, it is still an interesting topic for them. most do not understand it well, and other things that seem ordinary. The results of this community service show how enthusiastic they are about intensive teaching deepening. It is hoped that there will be an increase in understanding that can impact the congregation's spiritual life, which is expressed in daily life.